A Trans-acting Factor May Modify Age at Onset in Familial Amyloid Polyneuropathy ATTRV30M in Portugal - Alves-Ferreira, M (2018)
Although all familial amyloid polyneuropathy (FAP) ATTRV30M patients carry the same causative mutation, early (<40) and late-onset forms (≥50 years) of FAP may coexist in the same family. However, this variability in age at onset is still unexplained. To identify modifiers closely linked to the TTR locus that may in part be associated with age at onset of FAP ATTRV30M, in particular in a group of very early-onset patients (≤30 years) when compared with late-onset individuals. A clinical genetic study at a referral center comprising a sample of 910 Portuguese individuals includes 589 Val30Met carriers, 102 spouses, and 189 controls from the general population. Haplotype analysis was performed, using eight intragenic single nucleotide polymorphisms (SNPs) at the TTR locus. We compared haplotypes frequency in FAP samples and controls and in parent-offspring pairs using appropriated statistical analysis. Haplotype A was the most common in the general population. Noteworthy, haplotype C was more frequent in early-onset (<40) than in late-onset patients (≥50 years) (p = 0.012). When comparing allelic frequencies of each SNP within haplotype C between "very early" (≤30 years) and late-onset (≥50 years) cases, the A allele of rs72922947 was associated with an earlier onset (p = 0.009); this remained significant after a permutation-based correction. Also, the heterozygous genotype (GA) for this SNP was associated with a decrease in mean age at onset of 8.6 years (p = 0.014). We found a more common haplotype (A) linked to the Val30Met variant and a possible modulatory trans effect on age at onset. These findings may lead to potential therapeutical targets.